Editor's Note - Isa, Che Ruhana; Sulaiman, Ainin; Wai Meng, Chan (Asian Journal of Business and Accounting, 2016)
It is our pleasure to present the first issue of Volume 9 of the Asian Journal of Business and Accounting (AJBA). In this issue of AJBA, we have selected six papers for publication; all but one were the results of funded research. Four of the papers were authored by international scholars from emerging countries in Asia namely Thailand, Indonesia and Bangladesh, and two papers were authored by researchers from Malaysia. The first paper by Thanatawee examines the impact of open market share repurchases on stock liquidity of listed companies in Thailand over a period of 13 years, from 2002 to 2014. His research reveals that repurchasing shares can help increase stock liquidity but aggressive repurchasing over a short period of time has the contrary effect. This is consistent with the information asymmetry hypothesis which posits that managers are better informed thus, could use inside information to trade against outsiders, a governance issue. In the second paper, Wong and Hooy investigate the impact of elections in Indonesia, Malaysia and Thailand on stock market returns of government-owned banks from 2000 to 2013. Using event study methodology to capture the effect of short-horizon, the findings indicate that after elections, stock return rises more for government-owned banks as compared to non-government owned banks. This suggests that government-owned banks are reliant on their owners. Interestingly, this paper finds that the significance of government ownership on stock return, immediately after election, is highest in Malaysia followed by Thailand and Indonesia. The findings contribute to the extant literature on the political connections of financial firms where undertaken research is limited. The theme of governance is continued by papers written by Ahmed and Naima; Togok, Isa, and Zainuddin; and Utami and Nahartyo. One of the aims of good governance is to mitigate fraudulent financial reporting and opportunistic earnings management. In Ahmed and Naima, the Beneish Model (1999) was employed to identify the signs of earnings manipulation among firms in Bangladesh. Their findings suggest that the dominating indicative ratios relate to inflated revenues, capitalising expenses and overstating intangibles.